Recurrent cardiac tamponade in the course of neoplastic pericardial disease – the diagnostic and therapeutical difficulties - Wierusz-Wysocka, Bogna; Pisarczyk-Wiza, Dorota; Zozulińska, Dorota; Jedliński, Ireneusz (Contemporary Oncology/Współczesna Onkologia, 2001)
Both primary and secondary cardiac and pericardial neoplasms are observed very rarely. The most frequent tumor of the pericardium is mesothelioma. The prognosis is extremaly poor due to generally late presentation, inability to completely eradicate it surgically and its poor response to radiotherapy or chemotherapy. The authors describe the case of 66 year old woman with reccurent cardiac tamponade in the course of neoplastic pericardial disease. The authors also review the literature available in the Medline.